Closing The Loop of Cross-Fertilisation Transferring Human Factors Training from Aviation to Maritime - CROMIE, SAMUEL; LISTON, PAUL; Arrigoni, V.; Silvagni, S.; Ducci, M. (My University, 2016)
This paper outlines the application of a transfer and impact assessment methodology for the adaption of human factors training from the aviation domain to the maritime domain. Human factors training, as it currently exists in the maritime domain, is fragmented, unregulated and imperfectly aligned with operational and safety objectives. The SEAHORSE approach adopts a systematic method of transferring knowledge, learning and expertise from one sector to another (in this instance from aviation to maritime) by focusing on the innovation itself, along with the systemic aspects which support its adoption and long-term implementation. This paper details the methodology as adopted in transferring human factors training (as conceived in the aviation sector currently) to the maritime sector and the ways in which the impact of the implementation of human factors training for the maritime sector may be assessed.
SEAHORSE Conference on Maritime Safety and Human Factors
Keywords: Human factors training; Transfer of knowledge; Transfer of learning; Maritime; Aviation; HUMAN FACTORS; Maritime Safety; Organisational Learning; TRAINING; TRAINING-PROGRAMS; Transport